Morphological and morphometric features of cuboid bone - S Viveka; Suja S Kumar (Wolters Kluwer Medknow Publications, 2017)
Background and aims : Morphological and morphometric data of cuboid is of significance in creating 3D model of midfoot alignment and in understanding pathologies and instabilities in the region. There is minimal data on biometric values of cuboid. The objective of the study was to evaluate morphological variations in calcaneal articulating facet and metatarsal articulating facet The other obj ective was to report morphometric data of cuboid. Methodology: This descriptive study was conducted in the department of Anatomy, using 24 dry cuboid bones. Each bone was observed for pattern of articular surfaces. Articular surface of each bone was photographed and categorized, Presence of navicular facet was noted. Results: Pattern of calcaneal articular facet was classified into four types: 1A - concavo-convex facet with posteromedial projection and overall oval or remfonn shaped; IB- concavo-convex facet without posteromedial projection and rectangular shaped; 2A - plane facet with posteromedial projection and oval or reniform shaped; 2B - plane facet without posteromedial projection and rectangular shaped. Type 1 was the most common. Pattern of metatarsal articulating facet was classified into three groups: Concave - the edges of metatarsal articulating facet projected anteriorly making a depression for articulation of 4th and 5th metatarsal bones; Plane - articulating facet is flat; Convex - the articulating surface slopes posteriorly. Concave pattern was most common. Mean medial length of cuboid was 33.9 [±3.3] mm, lateral length was 17.9[±1.6]mm, height was 22[±1.5] mm, length index was 188.8, area of calcaneal articular facet was 124.9 [±10.9] mm2, area of metatarsal articulating facet was 91.9[±5.7]mm2, depth of peroneal groove was 1.83 [±1.3]mm. Conclusion: Morphological characterization of articular surfaces of cuboid, especially the calcaneal facet helps to understand the degree of movement at calcaneocuboidjoint and also joint pathologies.